BLOCKCHAIN-ENABLED SHARIAH-COMPLIANT SMART CONTRACTS FOR ISLAMIC FINANCE - Hendri Hermawan Adinugraha (PROFJES: Profetik Jurnal Ekonomi Syariah, 2026)
The rapid growth of Islamic finance highlights the need for innovative technologies that enhance efficiency while preserving strict Shariah compliance. Conventional Islamic financial instruments often rely on complex contractual structures, manual audits, and centralized intermediaries, which increase costs and reduce transparency. This study aims to examine how blockchain-enabled smart contracts can be designed and applied to support Shariah-compliant financial transactions and strengthen governance in Islamic finance. The research employs a systematic conceptual review method by synthesizing peer-reviewed journal articles, industry reports, and institutional publications published between 2018 and 2025. Relevant literature was analyzed thematically to assess smart contract architecture, Shariah compliance mechanisms, governance models, and regulatory implications. The findings indicate that blockchain-enabled smart contracts can operationalize Shariah principles by embedding prohibitions against riba, gharar, and non-asset-backed transactions directly into programmable code. This compliance-by-design approach enhances transparency, auditability, and trust, while reducing transaction costs and settlement delays. However, the study also identifies critical challenges, including divergent interpretations of Shariah, reliance on oracles, cybersecurity risks, and regulatory uncertainty. The study concludes that blockchain-enabled Shariah-compliant smart contracts offer a transformative pathway for Islamic finance, provided they are supported by robust governance frameworks, harmonized Shariah standards, and adaptive regulation.